Rekomendasi Penentuan Titik Tempat Penampungan Sampah Sementara Di Kecamatan Kedungkandang Kota Malang - Pratiwi, Eka Zuli; Meidiana, Christia; Wijayanti, Wawargita Permata (Fakultas Teknik, Universitas Brawijaya, 2018)
A waste management that supports 100-0-100 program of Ministry of Public Works and Housing (2015-2019) is one of main concerns of Malang city government. The community of Kedungkandang District has not been served fully by the waste management service. Only 37% of the Kedungkandang District Community which is served by waste management service or only 152,2 m 3 / day from the total volume of waste production which is 412,3 m 3 / day. This is not appropriate with the target of waste service in Malang City (100%). This target aimed to support the program of Public Work and Housing Ministry which is 100-0-100 that means 100% access to safe drinking water, 0% slum settlement and 100% access to sanitation service in 2015-2019. This research discusses the improvement the waste service area in Kedungkandang district by adding new transfer points and increasing the capacity of transfer points. The analyzes used in this study are the analysis of transfer point and waste collection tools conformity, overlay analysis, network analysis, operational waste transport analysis. The criteria needed to increase the waste service area in Kedungkandang District, and to determine the recommendation that will be applied. The criteria used is based on the regulation of Malang City no (10) 2010, PERMEN PU No (3) 2013 about the waste management infrastructure and Masterplan of Waste Management 2016, SNI 3242-2008 about the procedure of waste management in the settlement. The result of this research shows that the transfer points’ capacity which need to be expanded such as Cemorokandang transfer point, Kedungkandang transfer point, Lesanpuro transfer point, Arjowinangun transfer point, Danau Bratan transfer point, while the establishment of the new transfer points will be in Bumiayu Village, Tlogowaru Village, Kedungkandang Village, Cemorokandang Village, Wonokoyo Village.Keywords: Service area, transfer points, waste transport.